Adaptation of two measures of social support in argentinian university students - Zalazar Jaime, Mauricio Federico; Cupani, Marcos (Actualidades en Psicología, 2016)
Social support is an important construct in education which influences behavioral, cognitive and affective terms. Although there are numerous instruments to assess this construct, in Argentina there are no published scales to assess perceived support by students. Therefore, our aim was to adapt Social Support for Children and Adolescents (Malecki, Demaray & Elliot, 2003) and Academic Support (Lent et al., 2005) scales in college students. For this projectIn this regard, data from 551 students of different degrees from the National University of Cordoba (Argentina) was collected. For both instruments, results showed satisfactory internal consistency values (composite reliability, ρ > .70) and the original structure was replicated for each measure using confirmatory factor analysis. Limitations and new lines of research are suggested.